A Proposed Framework for Self-Financing in the Palestinian Universities and its Relation To the Quality of University Education - Nidal Hamdan Mustafa Al-Masri (University of Science and Technology, Yemen, 2017)
This research aimed to come out with a proposed framework for self-financing in the Palestinian universities and to investigate its  relation to the quality of university education by applying the framework to the upper and middle management in the universities so as to identify the nature of the relation and the impact of self-financing on the quality of university education. This was tested through the research hypotheses, A questionnaire was developed  and distributed to a sample of 100 employees, and 75 questionnaires were returned. The research concluded  with the following main findings: The best way to finance the universities is to rely on tuition fees, This would help universities to have a greater control over their decisions and to sell outputs of the best colleges when searching for self-financing by doing business. It was also found out that there is a positive relationship between self-financing and the quality of university education A proposed framework has been created to adopt its phases for the development of self-financing in the Palestinian universities to achieve a more effective quality university education. Keywords: Quality of university education, Self-financing, Universities